'A ondi queras': Ranchero identity construction by U.S. born Mexicans on Facebook. (November 2015) - Sidury Christiansen, M.
Abstract : This study describes how transnational second‐generation Mexican bilinguals use a stigmatized variety of Mexican Spanish to communicate on Facebook and construct an identity. The stereotyped features of this variety index a ranchero identity. Historically, ranchero is an ambivalent identity for Mexican society in general. On the one hand, ranchero culture is a positive reminiscence of Mexico's agrarian past, while on the other, rancheros, along with indigenous Mexicans, are at the bottom of the hierarchy in Mexican society. A discourse‐centered, ethnographic analysis of digitally mediated conversations demonstrates how language use allows participants to reminisce about their collective past, maintain Mexican identities tied to their ancestors, fit their identities to contemporary U.S. Mexican culture, and distance themselves from the stigma associated with the ranchero background.